+0  
 
0
73
1
avatar

3

(

2

n

4

)

1

4

n

=

3

4

(

n

+

4

)

n

=

Submit

 May 5, 2023
 #1
avatar+214 
+1

When written out in a string, your expression is:

 \(3(2n–4)– 1 4 n= 3 4 (n+4) n\)

\(6n-12-14n=34n^2+136n\)

\(34n^2+144n+12=0\)

\(17n^2+72n+6=0\)

\(n = {-72 \pm \sqrt{72^2-4\cdot17\cdot6} \over 34} \space \text{(Using the quadratic formula)}\)

\(n=\frac{-72 \pm \sqrt{4776}}{34}\)

\(n=\frac{-72 \pm 2\sqrt{1194}}{34}\)

\(n=\frac{-36 \pm \sqrt{1194}}{17}\)

Which is as simple as we can get it.

 May 5, 2023

3 Online Users

avatar